Photovoltaic devices based on nanocrystalline TiO2 and a fluorene-thiophene copolymer - Ravirajan, P.; Haque, S.A.; Poplavskyy, D.; Durcant, J.R.; Bradley, D.D.C.; Nelson, J. (My University, 2003)
We report studies of charge recombination and photovoltaic device performance in structures consisting of a fluorene-bithiophene co-polymer and nanocrystalline TiO2. Efficient photoinduced charge transfer is observed using a TiO2 film of high interfacial area while charge recombination is remarkably slow (∼ms). The influences of thickness, surface morphology, top contact material, light intensity and ionization potential of the polymer are studied. Quantum efficiencies of over 11% and monochromatic power conversion efficiencies of around 1 % are achieved.